ANALISIS TINGKAT KEPUASAN PASIEN RUMAH SAKIT DENGAN METODA IMPORTANCE PERFORMANCE ANALYSIS DAN POTENTIAL GAIN IN CUSTOMER VALUE INDEX - Muhammad lbnu Mastur; Mahma Matahari (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Problems on the quality of health services is not new. In contrast to the quality of goods and service quality is not so easy to determine but it can be felt. Therefore, It would need the regional public hospital in Yogyakarta to ﬁnd out how the level of customer satisfaction that can be used as a measure to make improvements in order to obtain an increase in customer satisfaction. To determine the performance of the regional public hospital in Yogyakarta represented by the value of the level of satisfaction, while in the repair of the attributes necessary to know the expectations of customers who are represented by the value of the interest rate. All activities were carried out using the method of Importance Performance Analysis (IPA).By 33 attributes asked to regional public hospital in Y ogyakarta are outpatient, Based on the value PGC V and Cartesian diagram turns out there are 12 attributes that need to be improved from the 19 attributes that need improvement. The value of new satisfaction rate reached 3.4 79 4.279 whilethe value of the level of importance of the maximum value 5. This proves that the regional public hospital in Yogyakarta services is still far from what is expected by the customer, or in other words, the customer was not satisﬁed. Advice author the regional public hospital in Yogyakarta immediately make improvement to the attributes which has the highest priority for it, for example,attribute Sensitivity employees toward customer complaints (patient), the waiting room is neat and clean, patient acceptance faster and easier.